Kedudukan Suami Berdasarkan Aturan Waris Bali Dalam Perkawinan Nyeburin Di Desa Adat Peliatan Ubud - Widianagari, Cok Istri Hemas; Krisnawati, I Gusti Ayu Agung Ari (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023), 2023)
The purpose of this study was to determine and analyze the husband's position in the Nyeburin marriage according to Awig-Awig in the Peliatan Traditional Village, Ubud and inheritance in the Nyeburin marriage, in the Peliatan Traditional Village, Ubud. Writing in this journal uses empirical research types, statutory approaches and legal concept analysis. Based on the results of the research, the following conclusions can be drawn: (1) the position of the husband as pradana in the marriage of nyeburin according to the village awig-awig, if the marriage is broken up whether the one who lives is still at his wife's residence or has returned to his original residence, no one has clearly discussed it on Indonesian positive law regulations; and (2) inheritance in the Nyeburin marriage in the Peliatan Traditional Village, the position of the male heir is clear, that is, he is not an heir, so his rights as an heir at his home have been lost, and he does not have rights as an heir at his wife's house.